Bistable copper(II) metallosurfactant as molecular machine for the preparation of hybrid silica-based porous materials - Walace D. do Pim; Tatiana A. Ribeiro-Santos; Ingrid S. Jardim; Mateus C.M. de Castro; Adriano H. Braga; Gustavo M. do Nascimento; Ildefonso Binatti; Humberto O. Stumpf; Eudes Lorençon; Maria H. Araujo; Cynthia L.M. Pereira (Materials & Design, 2018)
A pH-triggered bistable copper(II) complex acts as a molecular machine in which a molecular movement can be driven by the pH and the complex assumes deprotonate [Cu2L2]4− (1) or protonate form [Cu2(H2L)2] (2), where H2L = N,N′‑2,2′‑ethylenediphenylenebis(oxamic acid). 1 and 2 were used as templates during the hydrolysis of TEOS in aqueous medium at pH 12 and 5, respectively, resulting in meso (1@SiO2) and microporous (2@SiO2) silica-based hybrid materials without using conventional surfactants. The [Cu2L2]4− complex species leads to non-organized mesoporous silica nanostructures with specific surface area equal to 106 m2 g−1, while the microporous material 2@SiO2 presents surface area almost four times higher (409 m2 g−1). Furthermore, it was possible to reversibly deprotonate the oxamate-based ligand in 2@SiO2, leading to the formation of the tetra-anionic (pH = 12) species inside the microporous silica in a post-synthetic procedure. Both hybrid materials were characterized by FTIR, thermal analyses (TGA/DTA), PXRD, TEM, adsorption/desorption of N2, and TXRF in order to stablish a correlation between structure-catalytic activity. Due to its higher surface area, the efficiency of 2@SiO2 as heterogeneous catalyst in mild oxidation of benzyl alcohol (BzOH) by using H2O2 was evaluated, as well as its selectivity and recyclability. Keywords: Synthesis, Copper(II) complex, Hybrid porous silica, Materials characterization, Benzyl alcohol, Catalysis